Southernmost record of Megadolodus (Litopterna, Proterotheriidae, Megadolodinae) from the late Middle Miocene of Fitzcarrald, Peruvian Amazonia, and mesowear analysis of diet in megadolodine litopterns - Wilson, Oscar E. (2024)
Megadolodinae is a clade of tropical bunodont litopterns that includes three previously recognized species from Miocene fossil sites from northern South America. Here, we report an additional occurrence of Megadolodus molariformis from the Middle Miocene exposures at the Fitzcarrald arch (Peruvian Amazonia), based on dental material, which represents the southernmost record of the clade. This discovery further increases the faunal similarity between Fitzcarrald and the coeval La Venta fauna of Colombia. Given the convergent evolution of the bunodont dentition of megadolodines with suoids (Old World pigs and New World peccaries), we tested the hypothesis of frugivory in megadolodines with a mesowear angle approach using modern pigs and peccaries. These analyses differentiate the diet of modern suoids and suggest that megadolodines had a more abrasive diet than most of these taxa, except for the grazing warthogs. The dentition of megadolodines shows similar levels of abrasion to modern babirusas, thereby suggesting that the latter may represent an appropriate modern analog.